Inverted perovskite solar cell based on silicon oxide interface modification layer and manufacturing method thereof

By spin-coating the silicon oxide interface modification layer on the hole transport layer of the perovskite solar cell, the problem of difficulty in deposition of perovskite film is solved, the photoelectric conversion efficiency and coverage of perovskite solar cell is improved, and the photoelectric conversion efficiency and coverage of perovskite solar cell is promoted. Commercial application.

CN119300614APending Publication Date: 2025-01-10TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411411092.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In perovskite solar cells, the poor wetting of polar perovskite precursor solution on the bottom polar polymer hole transport layer makes it difficult to deposition perovskite film on the surface of the strongly hydrophobic hole transport layer, limiting the large Preparation and commercial application of area devices.

Method used

Using an inverted perovskite solar cell structure based on the silicon oxide interface modification layer, the coverage and interface contact performance of the perovskite active layer are improved by spin-coating the silicon oxide layer on the surface of the hole transport layer, and the scraping method is used to activate the SiO2 interface. Perovskite films were prepared on the modified layer.

Benefits of technology

The photoelectric conversion efficiency of perovskite solar cells has been significantly improved, the perovskite coverage and crystallinity have been enhanced, and the charge recombination has been reduced, thus realizing the commercial development of low-cost and high-efficiency perovskite solar cells has been achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119300614A_ABST
    Figure CN119300614A_ABST
Patent Text Reader

Abstract

The invention provides an inverted perovskite solar cell based on a silicon oxide interface modification layer and a manufacturing method thereof.The inverted perovskite solar cell sequentially comprises an anode layer, a hole transport layer, an interface modification layer, an active layer, an electron transport layer, a hole blocking layer and a silver electrode layer, the active layer is a perovskite active layer, and the thickness of the active layer is 200-800 nanometers; the interface modification layer is a silicon oxide layer, and the thickness of the interface modification layer is 1-10 nm; and the thickness of the hole transport layer is 10-50 nm. The photoelectric conversion efficiency of the perovskite solar cell provided by the invention is remarkably improved. The invention provides an effective scheme for commercialized development of low-cost and high-efficiency perovskite solar cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cells, and in particular relates to an inverted perovskite solar cell based on a silicon oxide (SiO2) interface modification layer and a preparation method thereof. Background Art

[0002] In recent years, perovskite solar cells (PSCs) have attracted extensive exploration in the scientific community due to their excellent optoelectronic properties, low raw material costs, and solution processing. How to achieve high-efficiency, high-stability, large-area perovskite solar cell devices at low cost is the focus of current research. However, most of the current efficient PSCs devices are prepared in a glove box using spin coating and other processes. This preparation method theoretically limits the preparation of large-area devices and increases the preparation cost.

[0003] However, the high temperature processing required for NIP device fabrication conflicts with low-cost commercialization and specific applications such as deposition on flexible plastic substrates and high-efficiency silicon heterojunction solar cell tandem structures. In recent years, PIN structured perovskite solar cells have attracted increasing attention due to their advantages such as low processing temperature, strong flexibility, low production cost and ease of use. However, it is quite difficult to deposit high-quality perovskite films on the surface of the strongly hydrophobic hole transport layer of PIN structured perovskite solar cells. This problem stems from the poor wettability of polar perovskite precursor solutions on the underlying polar polymer hole transport layer. Therefore, solving this problem in order to achieve full coverage and pinhole-free perovskite deposition by solution processing is very important for future commercial development. Summary of the invention

[0004] In view of the above problems, the present invention provides an inverted perovskite solar cell based on a SiO2 interface modification layer and a method for preparing the same, which can improve the coverage of the perovskite prepared by the scraping method on the hole transport layer in the perovskite solar cell by a simple and convenient method without affecting the electrical properties of the hole transport layer.

[0005] The inverted perovskite solar cell based on silicon oxide interface modification layer provided by the present invention comprises in sequence: an anode layer, a hole transport layer, an interface modification layer, an active layer, an electron transport layer, a hole blocking layer, a silver electrode layer,

[0006] in,

[0007] The active layer is a perovskite active layer, and its thickness is 200 to 800 nanometers;

[0008] The interface modification layer is a silicon oxide layer with a thickness of 1 to 10 nm;

[0009] The hole transport layer has a thickness of 10 to 50 nm.

[0010] further,

[0011] The perovskite active layer is a MAPbI3 layer;

[0012] The interface modification layer is a silicon oxide layer.

[0013] further,

[0014] The silicon oxide layer is prepared by a spin coating process.

[0015] further,

[0016] The hole transport layer is a PTAA layer or a Me-4PACz layer;

[0017] The electron transport layer is a PCBM layer, and its thickness is 10 to 60 nm;

[0018] The hole blocking layer is a BCP layer, and the thickness of the layer is 2-15 nm.

[0019] further,

[0020] The thickness of the active layer is 400 to 500 nanometers;

[0021] The thickness of the interface modification layer is 2 to 5 nm;

[0022] The thickness of the hole transport layer is 20 to 30 nm;

[0023] The thickness of the electron transport layer is 30 to 40 nm;

[0024] The thickness of the hole blocking layer is 5-10 nm.

[0025] The present invention also provides a method for preparing an inverted perovskite solar cell based on a silicon oxide interface modification layer, comprising the steps of:

[0026] 1. Spin coating a hole transport material precursor solution on a substrate to form a hole transport layer;

[0027] 2. Spin-coating a silicon oxide precursor solution on the surface of the hole transport layer to form a silicon oxide interface modification layer;

[0028] 3. Preparing a perovskite active layer on the interface modification layer by a doctor blade coating method;

[0029] 4. Spin coating an electron transport layer and a hole blocking layer on the surface of the perovskite active layer.

[0030] further,

[0031] In the step 1, the substrate is an indium tin oxide conductive glass substrate, the hole transport layer is a PTAA layer or a Me-4PACz layer,

[0032] When the hole transport layer is the PTAA layer, the step 1 comprises:

[0033] First, dissolve 3-8 mg of PTAA in 0.5-1.5 ml of toluene and shake on an oscillator for more than 1 min until the mixture is evenly mixed to obtain a PTAA solution.

[0034] 3b. Then, in a nitrogen glove box with a water and oxygen content of less than 0.01 ppm, a nitrogen purity of 99.999%, and a pressure of 3±2 mbar, 70-130 μl of PTAA solution is sucked with a pipette and dropped onto the indium tin oxide conductive glass substrate, and the coating is performed for 20-40 seconds at a spin coating speed of 3000-8000 rpm using a coating machine integrated in the glove box.

[0035] 3c, placing the indium tin oxide conductive glass substrate spin-coated with the PTAA solution on a heating table at 70-130 degrees Celsius in a second nitrogen glove box with the same working atmosphere as in step 3b, and annealing for 7-13 minutes to obtain the hole transport layer;

[0036] When the hole transport layer is the Me-4PACz layer, in the step 1, Me-4PACz is dissolved in ethanol and shaken sufficiently to obtain a Me-4PACz solution with a concentration of 0.3-0.7 mg / ml, and then, the Me-4PACz solution is used instead of the PTAA solution to perform the steps 3b and 3c to obtain the hole transport layer.

[0037] further,

[0038] In the step 2,

[0039] First, 70-130 μl of nano-silicon oxide dispersion was mixed with 3-8 ml of ethanol, and the mixture was fully shaken on the shaker for more than 1 minute until the mixture was uniform and transparent nano-silicon oxide dispersion was obtained.

[0040] In the nitrogen glove box, 160-240 μl of silicon oxide nano-dispersion liquid is pipetted with a pipette and dropped onto the indium tin oxide conductive glass substrate coated with the hole transport layer, and then the coating is performed by the coating machine at a spin coating speed of 3000-5000 rpm for 20-40 seconds.

[0041] The indium tin oxide conductive glass substrate spin-coated with the silicon oxide nano-dispersion liquid is placed on the heating stage at 70-130 degrees Celsius in the nitrogen glove box and annealed for 7-13 minutes to obtain the interface modification layer.

[0042] further,

[0043] In the step three,

[0044] First, 350-500 mg of PbI2, 120-200 mg of MAI, and 10-18 mg of PbCl2 are dissolved in 0.5-1.5 ml of a mixed solvent of DMF and DMSO to prepare a perovskite precursor mixed solution, wherein the volume ratio of DMF to DMSO in the mixed solvent of DMF and DMSO is 4:1, and then a stirring magnet is added to the perovskite precursor mixed solution and stirred with a magnetic stirrer at room temperature for more than 8 hours until the perovskite precursor mixed solution is uniformly mixed to obtain a perovskite precursor solution.

[0045] The perovskite precursor solution is coated on the surface of the SiO2 interface modification layer in an air environment by a scraping method, wherein the gap between the indium tin oxide conductive glass substrate and the scraping blade is fixed at 200-300 microns, and 12-25 microliters of the perovskite precursor solution is sucked by a pipette to fill the gap, and the perovskite precursor solution is spread over the entire SiO2 interface modification layer under the movement of the scraping blade, and the movement speed of the scraping blade is 12-25 mm per second, and then a vacuum crystallization device is used to perform auxiliary extraction for 0.5-1.5 minutes when the vacuum degree reaches below 2 Pa at room temperature to obtain an intermediate phase perovskite film on the indium tin oxide conductive glass substrate,

[0046] The mesophase perovskite film is then annealed on a heating stage at 80-150 degrees Celsius for 7-13 minutes to form a perovskite film, and then allowed to stand at room temperature for at least 3 minutes.

[0047] further,

[0048] In the step 1,

[0049] When the hole transport layer is the PTAA layer, the step 1 comprises:

[0050] 5 mg of PTAA was dissolved in 1 ml of toluene, and the mixture was shaken on an oscillator for more than 2 minutes until the mixture was uniformly mixed to obtain the PTAA solution;

[0051] In the step 3b, the coating is performed by spinning the coating machine at a speed of 5000 rpm for 30 seconds;

[0052] In the step 3c, the indium tin oxide conductive glass substrate spin-coated with the PTAA solution is placed on a heating table at 100 degrees Celsius in the second nitrogen glove box for annealing for 10 minutes to obtain the hole transport layer;

[0053] When the hole transport layer is the Me-4PACz layer, in the step 1, Me-4PACz is dissolved in ethanol and shaken thoroughly to obtain a Me-4PACz solution with a concentration of 0.5 mg / ml, and then the Me-4PACz solution is used to replace the PTAA solution, and the steps 3b and 3c are performed to obtain the hole transport layer.

[0054] In the step 2,

[0055] First, 100 microliters of nano-silicon oxide dispersion was mixed with 5 milliliters of ethanol, and the mixture was fully shaken on the shaker for more than 2 minutes until the mixture was uniform and transparent nano-silicon oxide dispersion was obtained;

[0056] In the nitrogen glove box, 200 microliters of silicon oxide nano-dispersion liquid was sucked by a pipette and dropped on the indium tin oxide conductive glass substrate coated with the hole transport layer, and then the coating was performed by the spin coater at a spin coating speed of 4000 rpm for 30 seconds;

[0057] The indium tin oxide conductive glass substrate spin-coated with the silicon oxide nano-dispersion liquid is placed on the heating stage at 100 degrees Celsius in the nitrogen glove box for annealing for 10 minutes to obtain the interface modification layer.

[0058] In the step three,

[0059] First, 437.94 mg of PbI2, 159 mg of MAI, and 13.9 mg of PbCl2 were dissolved in 1 ml of a mixed solvent of DMF and DMSO to prepare the perovskite precursor mixed solution.

[0060] The gap between the indium tin oxide conductive glass substrate and the doctor blade is fixed at 250 microns, and preferably 18 microliters of the perovskite precursor solution is sucked by a pipette to fill the gap. The moving speed of the doctor blade is 18 millimeters per second, and then a vacuum crystallization device is used to perform auxiliary extraction for 1 minute at room temperature when the vacuum degree reaches below 2 Pa to obtain the intermediate phase perovskite film.

[0061] The mesophase perovskite film was then annealed on a heating platform at 120 degrees Celsius for 10 minutes and then allowed to stand at room temperature for 5 minutes.

[0062] The present invention also provides an inverted perovskite solar cell based on a silicon oxide interface modification layer, which is prepared by the aforementioned method for preparing an inverted perovskite solar cell based on a silicon oxide interface modification layer.

[0063] The inverted perovskite solar cell based on the SiO2 interface modification layer provided by the present invention and the preparation method thereof have the following beneficial effects: first, the hole transport layer is hydrophobic, and a layer of silicon dioxide SiO2 material is spin-coated at the interface between the perovskite active layer and the hole transport layer, which can improve the surface wettability of the hole transport layer without losing the optical properties of the hole transport layer. Second, it helps to enhance the perovskite coverage, improve the crystallinity, facilitate charge transfer, and significantly reduce charge recombination. Third, the use of the SiO2 modification layer helps to improve the interface contact between the hole transport layer and the perovskite active layer. Better interface contact performance is very important for improving the photoelectric conversion efficiency of the perovskite solar cell. Therefore, the presence of the SiO2 interface modification material can significantly improve the photoelectric conversion efficiency of the perovskite solar cell.

[0064] The present invention proposes to spin-coat a silicon dioxide SiO2 material at the interface between the hole transport layer and the perovskite active layer, and the improvement of the wettability of the perovskite precursor solution significantly improves the photoelectric conversion efficiency of the perovskite solar cell prepared by the scraping method with a pin structure. The present invention provides an effective solution for the commercial development of low-cost, high-efficiency perovskite solar cells.

[0065] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0067] Figure 1 A schematic diagram of the structure of a perovskite solar cell according to an embodiment of the present invention is shown;

[0068] Figure 2 A physical picture of a perovskite film prepared by blade coating on an ITO / hole transport layer structure without a SiO2 interface modification layer as a comparative example is shown;

[0069] Figure 3 A physical picture of a perovskite film prepared by scraping on an ITO / hole transport layer / SiO2 structure with a SiO2 interface modification layer according to an embodiment of the present invention is shown;

[0070] Figure 4The scanning electron microscopic morphology of the perovskite film prepared by blade coating on the ITO / hole transport layer structure without SiO2 interface modification layer as a comparative example is shown;

[0071] Figure 5 The scanning electron microscopic morphology of the perovskite film prepared by scraping on the ITO / hole transport layer / SiO2 structure with the SiO2 interface modification layer according to the embodiment of the present invention is shown;

[0072] Figure 6 The JV curve of a perovskite solar cell without a SiO2 interface modification layer and scraped on an ITO / hole transport layer structure as a comparative example and the JV curve of a perovskite solar cell with a SiO2 interface modification layer and scraped on an ITO / hole transport layer / SiO2 structure according to an embodiment of the present invention are shown. DETAILED DESCRIPTION

[0073] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0074] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used in the specification of the application herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions. The terms "first", "second", "third", etc. in the specification and claims of this application or the above-mentioned figures are used to distinguish different objects, not to describe a specific order or a primary and secondary relationship. "Multiple" appearing in this application refers to more than two (including two).

[0075] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0076] The materials used in the present invention are:

[0077] Silicon dioxide (SiO2),

[0078] Poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine](PTAA),

[0079] [4-(3,6-dimethyl-9H-carbazol-9-yl)butyl]phosphoric acid (Me-4PACz),

[0080] [6,6]-phenyl-C61-butyric acid isomethyl ester (PCBM),

[0081] 2,9-Dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP),

[0082] Lead iodide (PbI2),

[0083] Methylammonium iodide (MAI),

[0084] Lead chloride (PbCl2),

[0085] N,N-dimethylformamide (DMF),

[0086] Dimethyl sulfoxide (DMSO),

[0087] Toluene, chlorobenzene, ethanol, isopropanol, acetone, deionized water.

[0088] Figure 1 The schematic diagram of the structure of the perovskite solar cell provided by the present invention is an inverted perovskite solar cell based on a SiO2 interface modification layer. Figure 1 , the glass substrate of the perovskite solar cell includes: indium tin oxide (ITO) layer, hole transport layer, interface modification layer, perovskite active layer, PCBM layer or Me-4PACz layer, BCP layer, silver electrode layer. Among them, the ITO layer is the anode layer; the hole transport layer is the PTAA layer or Me-4PACz layer, with a thickness of 10 to 50 nm, preferably 20 to 30 nm; the interface modification layer is the SiO2 layer, with a thickness of 1 to 10 nm, preferably 2 to 5 nm; the perovskite active layer is the MAPbI3 layer, with a thickness of 200 to 800 nm, preferably 400 to 500 nm; the PCBM layer is the electron transport layer, with a thickness of 10 to 60 nm, preferably 30 to 40 nm; the BCP layer is the hole blocking layer, with a thickness of 2 to 15 nm, preferably 5 to 10 nm; the silver electrode layer is the cathode layer, with a thickness of 70 to 130 nm, preferably 85 to 115 nm.

[0089] The perovskite solar cell can be made by the inverted perovskite solar cell preparation method based on SiO2 interface modification layer provided by the present invention (abbreviated as preparation method), and the preparation method includes the following steps.

[0090] S1. Select materials.

[0091] The materials required for preparing the perovskite solar cell are carefully selected and their quality, purity, concentration, fineness and precision are controlled:

[0092] Silicon dioxide (SiO2): nano-dispersion, particle size: 30nm, SiO2≈20%, solvent: ethanol,

[0093] Poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine](PTAA): solid powder, purity 99.99%,

[0094] [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphoric acid (Me-4PACz): solid powder, purity 99.99%,

[0095] [6,6]-phenyl-C61-butyric acid isomethyl ester (PCBM): solid powder, purity 99.99%,

[0096] 2,9-Dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP): solid powder, purity 99.99%, Lead iodide (PbI2): solid powder, purity 99.99%,

[0097] Methylammonium iodide (MAI): solid powder, purity 99.99%,

[0098] Lead chloride (PbCl2): solid powder, purity 99.99%,

[0099] N,N-dimethylformamide (DMF): liquid, purity 99.99%,

[0100] Dimethyl sulfoxide (DMSO): liquid, purity 99.99%,

[0101] Toluene: liquid, purity 99.99%,

[0102] Chlorobenzene: liquid, purity 99.99%,

[0103] Ethanol: liquid, purity 99.5%,

[0104] Isopropyl alcohol: liquid, purity 99.5%,

[0105] Acetone: liquid, purity 99.5%,

[0106] Deionized water: liquid, purity 99.99%,

[0107] Conductive glass ITO: solid, transmittance about 87%, square resistance 15Ω / m (ohm / meter). S2. Pretreatment of ITO conductive glass substrate in natural environment. Specifically includes the following steps:

[0108] 2a. Immerse the ITO conductive glass substrate in a mixed solution of Kangya glass cleaner and deionized water in a volume ratio of 1:5 for 8 hours (h);

[0109] 2b. Repeatedly scrub the front and back sides of the ITO conductive glass substrate and rinse with deionized water until a water film is formed on the front and back sides of the ITO conductive glass substrate;

[0110] 2c. Place the ITO conductive glass substrate in an ultrasonic cleaner, add tap water, and perform ultrasonic cleaning for 0.5 h;

[0111] 2d. Place the ITO conductive glass substrate in an ultrasonic cleaner, add deionized water, and perform ultrasonic cleaning for 0.5 h.

[0112] 2e. Place the ITO conductive glass substrate in an ultrasonic cleaner, add ethanol, and perform ultrasonic cleaning for 0.5 h;

[0113] 2f. Place the ITO conductive glass substrate in an oven and dry it at 130 degrees for about 30 minutes. Take it out and place it in a natural environment to cool to room temperature.

[0114] 2g. Place the cleaned ITO conductive glass substrate in a UV ozone cleaning machine for 15 minutes (min).

[0115] S3, spin coating the hole transport material precursor solution on the ITO conductive glass substrate to form a hole transport layer on the ITO conductive glass substrate. Specifically comprising the following steps:

[0116] 3a. First, 3-8 mg, preferably 5 mg, of PTAA is dissolved in 0.5-1.5 mL, preferably 1 mL, of toluene, and the mixture is shaken on an oscillator for more than 1 min, preferably more than 2 min, until the mixture is uniformly mixed to obtain a PTAA solution.

[0117] 3b. Then, in a nitrogen glove box with a water and oxygen content of less than 0.01 PPm (parts per million), a nitrogen purity of 99.999%, and an air pressure of 3±2 mbar, 70-130 μL, preferably 100 μL, of PTAA solution is pipetted with a liquid transfer gun and dropped onto the ITO conductive glass sheet treated with UV ozone, i.e., the ITO conductive glass substrate. The coating is performed for 20-40 seconds, preferably 30 seconds, using a coating machine integrated in the glove box at a spin coating speed of 3000-8000 rpm, preferably 5000 rpm.

[0118] 3c. Place the ITO conductive glass sheet spin-coated with PTAA in a second nitrogen glove box with the same working atmosphere as step 3b (i.e., the same water and oxygen content, the same nitrogen purity and air pressure) at 70-130 degrees Celsius (°C), preferably at 100°C, and anneal for 7-13 minutes, preferably 10 minutes, to obtain a PTAA hole transport layer.

[0119] The hole transport material PTAA used can be replaced by Me-4PACz. In this case, the preparation method of the Me-4PACz hole transport layer is: dissolve Me-4PACz in ethanol, shake it thoroughly to obtain a Me-4PACz solution with a concentration of 0.3-0.7 mg / mL, preferably 0.5 mg / mL, and then replace the PTAA solution with the Me-4PACz solution, and perform steps 3b and 3c to obtain the hole transport layer.

[0120] S4, spin coating SiO2 precursor solution on the surface of PTAA hole transport layer to form SiO2 modified layer on the hole transport layer. The specific steps are:

[0121] 4a. First, take 70-130 μL, preferably 100 μL, of the nano-SiO2 dispersion and mix it with 3-8 mL, preferably 5 mL, of ethanol, and oscillate it on an oscillator for more than 1 min, preferably more than 2 min until the mixture is evenly mixed to obtain a uniform and transparent SiO2 nano-dispersion.

[0122] 4b. In the nitrogen glove box described in step S3b, 160-240 μL, preferably 200 μL, of the SiO2 solution, i.e., the SiO2 nanodispersion, is pipetted with a pipette and dropped onto an ITO conductive glass sheet coated with a PTAA or Me-4PACz hole transport layer, followed by spin coating with a coating machine at a spin coating speed of 3000-5000 rpm, preferably 4000 rpm, for 20-40 s, preferably 30 s.

[0123] 4c. Place the ITO conductive glass sheet spin-coated with SiO2 on a heating table at 70-130°C, preferably 100°C in the nitrogen glove box and anneal for 7-13 minutes, preferably 10 minutes, to obtain a SiO2 interface modification layer.

[0124] S5, preparing a MAPbI3 perovskite active layer on the SiO2 interface modification layer by a doctor blade method. This step can be performed in the air and specifically includes the following steps:

[0125] 5a. First, 350-500 mg, preferably 437.94 mg of PbI2, 120-200 mg, preferably 159 mg of MAI, and 10-18 mg, preferably 13.9 mg of PbCl2 are dissolved in 0.5-1.5 mL, preferably 1 mL of a mixed solvent of DMF and DMSO to prepare a perovskite precursor mixed solution, wherein the volume ratio of DMF and DMSO in the mixed solvent of DMF and DMSO is 4:1. Then, a stirring magnet is added to the perovskite precursor mixed solution and stirred with a magnetic stirrer at room temperature for more than 8 hours until the mixture is uniformly mixed to obtain a perovskite precursor solution.

[0126] 5b. The precursor solution is coated on the surface of the SiO2 interface modification layer in an air environment by a doctor blade method. The gap between the substrate and the doctor blade is fixed to 200-300 μm, preferably 250 μm, and 12-25 μL, preferably 18 μL, of the perovskite precursor solution is sucked with a pipette to fill the gap. The perovskite precursor solution is spread over the entire SiO2 interface modification layer on the substrate at the same temperature as the air environment under the movement of the doctor blade. The moving speed of the doctor blade is 12-25 millimeters per second (mm / s), preferably 18 mm / s, and then a vacuum crystallization device such as a vacuum crystallizer is used to perform auxiliary extraction for 0.5-1.5 min, preferably 1 min at room temperature when the vacuum degree reaches below 2 Pa (Pascals) to obtain an intermediate phase perovskite film.

[0127] 5c. The intermediate phase perovskite film is then annealed on a heating platform at 80-150° C., preferably at 120° C., for 7-13 min, preferably 10 min, to form a perovskite film with high crystallinity, and then allowed to stand at room temperature for at least 3 min, preferably 5 min.

[0128] S6, spin coating the electron transport layer and the hole blocking layer on the surface of the perovskite active layer. Specifically comprising the following steps:

[0129] 6a. First, dissolve 15-25 mg, preferably 20 mg, of PCBM in 0.5-1.5 mL, preferably 1 mL, of chlorobenzene, and shake thoroughly on an oscillator for more than 1 min, preferably more than 2 min, until the mixture is uniformly mixed to obtain a PCBM solution.

[0130] 6b. Then, 20-40 μL, preferably 30 μL, of the PCBM solution is pipetted and dropped onto the substrate on which the perovskite active layer is prepared. In the nitrogen glove box described in step S3b, a coating machine is used to spin coat the solution at a speed of 3000-7000 rpm, preferably 5000 rpm, for 20-40 s, preferably 30 s, to obtain a PCBM electron transport layer.

[0131] 6c. Then, 0.3-0.7 mg, preferably 0.5 mg, of BCP is dissolved in 7-13 mL, preferably 10 mL, of isopropanol, and heated on a hot plate at 70-130° C., preferably 100° C., for 1 h, preferably more than 2 h, until the BCP is completely dissolved. The mixture is fully shaken on an oscillator for 1 min, preferably more than 2 min, until the mixture is evenly mixed to obtain a BCP solution.

[0132] 6d. Then, 7-13 μL, preferably 10 μL, of BCP solution is pipetted and dropped onto the substrate on which the PCBM electron transport layer is completed. In the nitrogen glove box, a coating machine is used to perform dynamic spin coating at a spin coating speed of 3000-5000 rpm, preferably 4000 rpm, for 20-40 s, preferably 30 s.

[0133] S7, using a vacuum evaporation furnace to evaporate a silver cathode electrode on the substrate on which the BCP has been spin-coated. The cathode material is formed by vacuum thermal evaporation of silver Ag, with an evaporation rate of 0.08-0.16 nanometers per second (nm / s), preferably 0.12nm / s, and a film thickness of 100nm±30nm, preferably 100nm±15nm. After the metal electrode is evaporated, an inverted perovskite solar cell modified by SiO2 is prepared by a scraping method.

[0134] Figure 2 A physical picture of a perovskite film prepared by scraping on an ITO / hole transport layer structure without a SiO2 interface modification layer as a comparative example is shown. Figure 3 The actual picture of the perovskite film prepared by scraping on the ITO / hole transport layer / SiO2 structure with SiO2 interface modification layer provided by the present invention is shown. Figure 2 and Figure 3 It can be seen that the perovskite film coated on the SiO2 interface modification layer has better coverage.

[0135] Figure 4 The scanning electron microscopic morphology of the perovskite film prepared by scraping on the ITO / hole transport layer structure without SiO2 interface modification layer as a comparative example is shown. Figure 5 The scanning electron micrograph of the perovskite film prepared by scraping on the ITO / hole transport layer / SiO2 structure with SiO2 interface modification layer provided by the present invention is shown. Figure 4 and Figure 5 It can be seen that the perovskite film coated on the SiO2 interface modification layer is smoother and denser, and the grain size is more uniform.

[0136] Figure 6The JV curve of a perovskite solar cell without a SiO2 interface modification layer and scraped on an ITO / hole transport layer structure as a comparative example and the JV curve of a perovskite solar cell with a SiO2 interface modification layer and scraped on an ITO / hole transport layer / SiO2 structure provided by the present invention are shown. Figure 6 It can be seen that compared with the perovskite solar cells with hole transport layers prepared based on the existing technology, the short-circuit current, open-circuit voltage and fill factor of the perovskite solar cells prepared by the air scraping method based on the SiO2-modified hole transport layer are significantly improved, and the photovoltaic performance of the device is significantly improved.

[0137] pass Figures 2 to 6 It can be seen that modifying the hole transport layer with silicon dioxide SiO2 improves the coverage of perovskite on the hole transport layer and increases the PCE of the device.

[0138] The present invention proposes to spin-coat a silicon dioxide SiO2 material at the interface between the hole transport layer and the perovskite active layer, and the improvement of the wettability of the perovskite precursor solution significantly improves the photoelectric conversion efficiency of the perovskite solar cell prepared by the scraping method with a pin structure. The present invention provides an effective solution for the commercial development of low-cost, high-efficiency perovskite solar cells.

[0139] Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent substitutions for some of the technical features therein; and these modifications or substitutions do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An inverted perovskite solar cell based on a silicon oxide interface modification layer, characterized in that: Including in order: Anode layer, hole transport layer, interface modification layer, active layer, electron transport layer, hole blocking layer, silver electrode layer, in, The active layer is a perovskite active layer, and its thickness is 200 to 800 nanometers; The interface modification layer is a silicon oxide layer with a thickness of 1 to 10 nm; The hole transport layer has a thickness of 10 to 50 nm.

2. The inverted perovskite solar cell based on the silicon oxide interface modification layer according to claim 1, characterized in that: The perovskite active layer is a MAPbI3 layer; The interface modification layer is a silicon oxide layer.

3. The inverted perovskite solar cell based on silicon oxide interface modification layer according to claim 1, characterized in that: The silicon oxide layer is prepared by a spin coating process.

4. The inverted perovskite solar cell based on the silicon oxide interface modification layer according to claim 3, characterized in that: The hole transport layer is a PTAA layer or a Me-4PACz layer; The electron transport layer is a PCBM layer, and its thickness is 10 to 60 nm; The hole blocking layer is a BCP layer, and the thickness of the layer is 2-15 nm.

5. The inverted perovskite solar cell based on the silicon oxide interface modification layer according to claim 4, characterized in that: The thickness of the active layer is 400 to 500 nanometers; The thickness of the interface modification layer is 2 to 5 nm; The thickness of the hole transport layer is 20 to 30 nm; The thickness of the electron transport layer is 30 to 40 nm; The thickness of the hole blocking layer is 5-10 nm.

6. A method for preparing an inverted perovskite solar cell based on a silicon oxide interface modification layer, characterized in that: Includes steps:

1. Spin coating a hole transport material precursor solution on a substrate to form a hole transport layer; 2. Spin-coating a silicon oxide precursor solution on the surface of the hole transport layer to form a silicon oxide interface modification layer; 3. Preparing a perovskite active layer on the interface modification layer by a doctor blade coating method; 4. Spin coating an electron transport layer and a hole blocking layer on the surface of the perovskite active layer.

7. The method for preparing an inverted perovskite solar cell based on a silicon oxide interface modification layer according to claim 6, characterized in that: In the step 1, the substrate is an indium tin oxide conductive glass substrate, the hole transport layer is a PTAA layer or a Me-4PACz layer, When the hole transport layer is the PTAA layer, the step 1 comprises: First, dissolve 3-8 mg of PTAA in 0.5-1.5 ml of toluene and shake on an oscillator for more than 1 min until the mixture is evenly mixed to obtain a PTAA solution. 3b. Then, in a nitrogen glove box with a water and oxygen content of less than 0.01 ppm, a nitrogen purity of 99.999%, and a pressure of 3±2 mbar, 70-130 μl of PTAA solution is sucked with a pipette and dropped onto the indium tin oxide conductive glass substrate, and the coating is performed for 20-40 seconds at a spin coating speed of 3000-8000 rpm using a coating machine integrated in the glove box. 3c, placing the indium tin oxide conductive glass substrate spin-coated with the PTAA solution on a heating table at 70-130 degrees Celsius in a second nitrogen glove box with the same working atmosphere as in step 3b, and annealing for 7-13 minutes to obtain the hole transport layer; When the hole transport layer is the Me-4PACz layer, in the step 1, Me-4PACz is dissolved in ethanol and shaken sufficiently to obtain a Me-4PACz solution with a concentration of 0.3-0.7 mg / ml, and then, the Me-4PACz solution is used instead of the PTAA solution to perform the steps 3b and 3c to obtain the hole transport layer.

8. The method for preparing an inverted perovskite solar cell based on a silicon oxide interface modification layer according to claim 7, characterized in that: In the step 2, First, 70-130 μl of nano-silicon oxide dispersion was mixed with 3-8 ml of ethanol, and the mixture was fully shaken on the shaker for more than 1 minute until the mixture was uniform and transparent nano-silicon oxide dispersion was obtained. In the nitrogen glove box, 160-240 μl of silicon oxide nano-dispersion liquid is pipetted with a pipette and dropped onto the indium tin oxide conductive glass substrate coated with the hole transport layer, and then the coating is performed by the coating machine at a spin coating speed of 3000-5000 rpm for 20-40 seconds. The indium tin oxide conductive glass substrate spin-coated with the silicon oxide nano-dispersion liquid is placed on the heating stage at 70-130 degrees Celsius in the nitrogen glove box and annealed for 7-13 minutes to obtain the interface modification layer.

9. The method for preparing an inverted perovskite solar cell based on a silicon oxide interface modification layer according to claim 8, characterized in that: In the step three, First, 350-500 mg of PbI2, 120-200 mg of MAI, and 10-18 mg of PbCl2 are dissolved in 0.5-1.5 ml of a mixed solvent of DMF and DMSO to prepare a perovskite precursor mixed solution, wherein the volume ratio of DMF to DMSO in the mixed solvent of DMF and DMSO is 4:1, and then a stirring magnet is added to the perovskite precursor mixed solution and stirred with a magnetic stirrer at room temperature for more than 8 hours until the perovskite precursor mixed solution is uniformly mixed to obtain a perovskite precursor solution. The perovskite precursor solution is coated on the surface of the SiO2 interface modification layer in an air environment by a scraping method, wherein the gap between the indium tin oxide conductive glass substrate and the scraping blade is fixed at 200-300 microns, and 12-25 microliters of the perovskite precursor solution is sucked by a pipette to fill the gap, and the perovskite precursor solution is spread over the entire SiO2 interface modification layer under the movement of the scraping blade, and the movement speed of the scraping blade is 12-25 mm per second, and then a vacuum crystallization device is used to perform auxiliary extraction for 0.5-1.5 minutes when the vacuum degree reaches below 2 Pa at room temperature to obtain an intermediate phase perovskite film on the indium tin oxide conductive glass substrate, The mesophase perovskite film is then annealed on a heating stage at 80-150 degrees Celsius for 7-13 minutes to form a perovskite film, and then allowed to stand at room temperature for at least 3 minutes.

10. The method for preparing an inverted perovskite solar cell based on a silicon oxide interface modification layer according to claim 9, characterized in that: In the step 1, When the hole transport layer is the PTAA layer, the step 1 comprises: 5 mg of PTAA was dissolved in 1 ml of toluene, and the mixture was shaken on an oscillator for more than 2 minutes until the mixture was uniformly mixed to obtain the PTAA solution; In the step 3b, the coating is performed by spinning the coating machine at a speed of 5000 rpm for 30 seconds; In the step 3c, the indium tin oxide conductive glass substrate spin-coated with the PTAA solution is placed on a heating table at 100 degrees Celsius in the second nitrogen glove box for annealing for 10 minutes to obtain the hole transport layer; When the hole transport layer is the Me-4PACz layer, in the step 1, Me-4PACz is dissolved in ethanol and shaken thoroughly to obtain a Me-4PACz solution with a concentration of 0.5 mg / ml, and then the Me-4PACz solution is used to replace the PTAA solution, and the steps 3b and 3c are performed to obtain the hole transport layer. In the step 2, First, 100 microliters of nano-silicon oxide dispersion was mixed with 5 milliliters of ethanol, and the mixture was fully shaken on the shaker for more than 2 minutes until the mixture was uniform and transparent nano-silicon oxide dispersion was obtained; In the nitrogen glove box, 200 microliters of silicon oxide nano-dispersion liquid was sucked by a pipette and dropped on the indium tin oxide conductive glass substrate coated with the hole transport layer, and then the coating was performed by the spin coater at a spin coating speed of 4000 rpm for 30 seconds; The indium tin oxide conductive glass substrate spin-coated with the silicon oxide nano-dispersion liquid is placed on the heating stage at 100 degrees Celsius in the nitrogen glove box for annealing for 10 minutes to obtain the interface modification layer. In the step three, First, 437.94 mg of PbI2, 159 mg of MAI, and 13.9 mg of PbCl2 were dissolved in 1 ml of a mixed solvent of DMF and DMSO to prepare the perovskite precursor mixed solution. The gap between the indium tin oxide conductive glass substrate and the doctor blade is fixed at 250 microns, and preferably 18 microliters of the perovskite precursor solution is sucked by a pipette to fill the gap. The moving speed of the doctor blade is 18 millimeters per second, and then a vacuum crystallization device is used to perform auxiliary extraction for 1 minute at room temperature when the vacuum degree reaches below 2 Pa to obtain the intermediate phase perovskite film. The mesophase perovskite film was then annealed on a heating platform at 120 degrees Celsius for 10 minutes, and then allowed to stand at room temperature for 5 minutes.

11. An inverted perovskite solar cell based on a silicon oxide interface modification layer, characterized in that: The inverted perovskite solar cell is prepared by the method for preparing an inverted perovskite solar cell based on a silicon oxide interface modification layer as described in any one of claims 6 to 10.